Age-related brain atrophy in cats without apparent neurological and behavioral signs using voxel-based morphometry - Hamamoto, Yuji; Yu, Yoshihiko; Asada, Rikako; Mizuno, Satoshi; Hasegawa, Daisuke (Frontiers in Veterinary Science, 2022)
Introduction Brain atrophy is observed with aging and may cause cognitive decline or dysfunction. Aging cats may demonstrate behavioral changes related to cognitive dysfunction. In the clinical veterinary field, although the conventional region of interest method by manual or semiauto tracing on magnetic resonance imaging is used to detect atrophy of regional structures, such as the hippocampus, it is difficult to assess atrophy globally. Voxel-based morphometry (VBM) has been developed to detect global and regional abnormalities in humans. The purpose of the present study investigates whether the feline brain volume decreases with aging using VBM analysis. Materials A total of 65 cats, aged 17–200 months, without apparent neurological and behavioral signs were included in the statistical analysis. Results We observed that the gray matter in the bilateral parietal lobes was decreased significantly with aging. The regions that showed decreased volume included the right postcruciate, cingulate gyrus, rostral suprasylvian/ectosylvian gyri, and the left postcruciate gyrus. No significant reduction in white matter was observed. Together, our results show that age-related brain atrophy can be detected using VBM analysis. Discussion The age-related atrophy of the parietal cortex may not cause neurological and behavioral signs in cats. Therefore, veterinarians should consider age when assessing the relation between morphometric and functional abnormalities of the parietal cortex in cats.